Kegagalan dan Keberhasilan Mediasi dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Kajen Tahun 2017 - Khusni Zulkfa, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The type of research that the author uses in this study is a type of field research. This study uses a qualitative approach, where this research seeks to explain in detail the discussion as an answer to the main problem. The process of collecting qualitative data, which generally focuses on interviews and participatory observation, analyzes the data in the form of textual analysis of the transcripts or field notes. Based on the results of research conducted, the Mediator has carried out the mediation process in accordance with PERMA No.1 of 2016. In its implementation, the mediator also always strives for peace between the parties in a case. However, in reality the success and failure of the mediation lies in the problems brought by the parties to the court, not from the mediator in charge. Most of the problems brought by the litigants are problems that are difficult to solve, such as: The presence of a third party, heartache (economic factors and harsh words), domestic violence (KDRT) and long-standing problems.